Quantifying the effects of plant density on soybean lodging resistance and growth dynamics in maize-soybean strip intercropping - Wang, Li; Cheng, Bin; Zhou, Tao; Jing, Shuzhong; Liu, Ranjin; Gao, Yang; Deng, Chaoyang; Ye, Wenwei; Luo, Zhigang; Raza, Ali; Xu, Mei; Wang, Wenyan; et al. (Frontiers in Plant Science, 2023)
Shading-induced soybean stem lodging is a prevalent concern in the maize (Zea mays L.)-soybean (Glycine max L. Merr.) strip intercropping system, leading to a substantial decline in yield. Nevertheless, the associations between soybean growth, stem lodging, and yield formation in this scenario remain unclear. To investigate this, the logistic and beta growth models were utilized to analyze the growth process of soybean organs (stems, leaves, branches, and pods) and the accumulation of carbohydrates (lignin, cellulose, and sucrose) at three planting densities (8.5, 10, and 12.5 plants m −2 ) in both strip intercropping and skip strip monoculture systems. The results indicate that shading stress caused by maize in the intercropping system reduced lignin and cellulose accumulation in soybean stems, thus decelerating soybean organ growth compared to monoculture. Furthermore, intercropped soybean at higher planting density (PD3) exhibited a 28% reduction in the maximum dry matter growth rate (cm) and a 11% decrease in the time taken to reach the maximum dry matter growth rate (te) compared to the lower planting density (PD1). Additionally, a 29% decrease in the maximum accumulation rate (cmax) of sucrose, lignin, and cellulose was observed, along with a 13% decrease in the continuous accumulation time (tc) of these carbohydrates in intercropped soybean at PD3. Interspecific and intraspecific shading stress led to a preferential allocation of assimilates into soybean stems, enhancing plant height during the initial stage, while at later stages, a greater proportion of sucrose was allocated to leaves. Consequently, this hindered the conversion of sucrose into lignin and cellulose within the stems, ultimately resulting in a reduction in the lodging